PENGARUH PENGGUNAAN BEBERAPA MULSA TERHADAP SERANGAN ULAT BAWANG Spodoptera exigua (Lepidoptera: Noctuidae) PADA TANAMAN BAWANG MERAH (Allium ascalonicum) DI DESA BOLU POUNTU JAYA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Khoirun Joko Widodo; Muhammad Yunus; Shahabuddin Shahabuddin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
The purpose study was to determine the effect of various kinds of mulch on the    infestation of Spodoptera exigua (Lepidoptera: Noctuidae) in onion crops. This research was conducted in the onion crop  in the  Bolu Pountu Jaya village, Sigi Biromaru Regency, Sigi Subdistric from January to March 2014.  The study was using a randomized complete block design which consists of 4 treatments namely: without mulch (P0), rice straw mulch 4,5 kg/plot (P1), cocoa husk mulch 4,5 kg/plot (P2) and plastic mulch (P3).  Observation variables consist      of pest attack rate,  crops height and production.  The results showed that the mulching treatment have a significant effect of attack intensity of S.exigua on onion crop, but has no effect on crop height and production. Onion crops that grown without using a mulch have a high rate attack from pest than the onion without mulching. Key Words : Onion, mulch, Spodoptera exigua.